The fragmented recognition of unilateral termination in consumer contracts in Chilean Consumer Law - Isler Soto, Erika (2024)
The article analyzed the regulation of the unilateral termination of the contract in Chilean Consumer Law, reaching the conclusion that its treatment is fragmentary and inorganic. However, unilateral termination is regulated whether it is based on the law or based on the contract. In the first case, it is granted solely and imperatively to the consumer, as a weak subject of the consumer relationship, under the figures of retract and withdrawal. There are, however, important differences between one and the other, linked to the eventual validity of an expiration period, the way in which it operates and its scope of application. The unilateral withdrawal enshrined by the pact is considered illicit if it is established exclusively in favor of the entrepreneur and lawful if its beneficiary is the consumer. When the power is conferred on both parties of the consumer relationship, its legality will have to be judged according to whether or not it generates a significant imbalance for the parties and whether it complies with the standards of good faith.